Innovative biological water treatment for the removal of elevated ammonia. Issue 9 (1st September 2013) - Lytle, Darren A.; White, Colin; Williams, Daniel; Koch, Lauren; Nauman, Emily
Abstract : The objective of this work was to demonstrate the effectiveness of an innovative and simple biological water treatment approach for removing 3.3 mg nitrogen (N) per litre ammonia and iron from water using a pilot study conducted at a utility in Iowa. Biological water treatment can be an effective approach to addressing low ammonia levels; however, providing adequate oxygen to address source water ammonia levels greater than 1.5 mg/L N is challenging. The treatment consisted of a biological "contactor" combined with aeration, followed in series with a dual granular media filter. Orthophosphate was necessary to satisfy biological nutrient requirements, and maintaining near‐saturated dissolved oxygen levels throughout the contactor was important. The pilot project demonstrated that a contactor and filter operated at loading rates of 2.2 gpm/sq ft and 2.0 gpm/sq ft, respectively, met desired finished water quality objectives. The contactor alone was able to completely biologically oxidize all of the ammonia to nitrate. Contactor maintenance was minimal.